Proses Pembuatan Tahu Putih di Desa Sei Bamban Dusun Tahun X Kec. Batang Serangan Kab. Langkat - Habibunnisa Habibunnisa; Widiya Tri Utami; Dwie Jihan Fadillah; Lana Paujiah Nst; Bella Villanda; Rabiah Afifah Daulay (Sekolah Pascasarjana Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
The purpose of this research is to describe business management and to study the tofu production environment. to know more about the production and distribution of tofu at the Tofu Factory, Batang Serangan District, Langkat Regency Year X, Sei Bamban Hamlet. Surveys with interviews used to collect data are used in this type of research. The tofu factory visited is a family business that makes tofu by processing soybeans. The four business functions of the tofu factory are marketing, production/operations, accounting/finance, and human resources. The results showed that tofu is a fermented food product that has economic value and protein needs for the community due to increased market demand. To make tofu, a chemical reaction occurs during the fermentation process, just like in the manufacturing process. Keywords: manufacturing process, white tofu, Sei Bamban, Batang Serangan